The Muslim Question in Canada: A Story of Segmented Integration By Abdolmohammad Kazemipur (Vancouver: University of British Columbia Press, 2014. 209 pages.) (American Journal of Islam and Society, 2016)
Considering that in the 2015 Federal Election, candidates were often talkingabout Muslims and their relationship to Canada, whether from an empatheticand supportive position or from a negative and racist position, Kazemipur’sbook could not be more welcome and timely. While many of us in the Muslimcommunity wish we were not part of a “question” that needed debating anddiscussing, Kazemipur’s title is, regrettably, very consciously and aptly chosen,for it refers back to the debates in Europe at the turn of the nineteenthcentury about the “Jewish Question.” The author notes, as others have, thatcontemporary debates about “illiberal Muslims” with strange customs whocannot and will not “integrate” into Canadian society mirror those about Jewsin that era (pp. 7-8), and proposes to study this particular community througha much needed sociological lens. The book is very well-written, accessible,methodologically and theoretically sophisticated, and enormously useful –anyone who wants to talk about the Muslim experience in Canada will find itinsightful and indispensable for coming to terms with day-to-day realities ofthose experiences.Kazemipur rightly points out that this “Muslim” question is not fruitfullyapproached through the paradigm proposed by Samuel Huntington and likemindedscholars, namely, “culture,” which forms the basis of a “Muslim exceptionalism”(p. 5) and explains the “inability” of Muslims to integrate intowestern democracies. This approach, he argues, “grossly oversimplifies aBook Reviews 127complex and multifaceted problem” and “removes the possibility that themainstream population might have to take some moral responsibility for it”(p. 5). Integration is a relationship among different peoples. Thus he alsopoints out, although not until the end of the book, that trying to understandthese Muslims’ situation by focusing upon Islamic theology is less useful than ...